The Contribution of Shape Features and Demographic Variables to Disembedding Abilities - Cappello, Elisa Morgana; Lettieri, Giada; Malizia, Andrea Patricelli; d’Arcangelo, Sonia; Handjaras, Giacomo; Lattanzi, Nicola; Ricciardi, Emiliano; Cecchetti, Luca (Frontiers in Psychology, 2022)
Humans typically perceive visual patterns in a global manner, and are remarkably capable of extracting object shapes based on properties such as proximity, closure, symmetry, and good continuation. Notwithstanding people’s attitude toward perceptual grouping, the research highlighted differences in disembedding performance across individuals, summarized by the field dependence/independence dimension. Previous studies revealed that age and educational attainment explain part of this variability, whereas the role of sex is still highly debated. Also, which stimulus features primarily influence inter-individual variations in perceptual grouping has still to be fully determined. Building upon these premises, we assessed the role of age, level of education and sex on performance at the Leuven-Embedded Figure Test - a proxy of disembedding abilities - in a sample of 391 cisgender individuals. We also investigated whether stimulus symmetry, closure, complexity, and continuation relate to task accuracy as a function of personal characteristics. Overall, target asymmetry and continuation with the embedding context increase task difficulty, and target complexity demonstrates a U-shaped relationship with disembedding performance. Concerning demographic data, we report that sex, age, and educational attainment, are significantly associated with disembedding abilities. Males benefit more from target symmetry and closure and are better at recognizing shapes when the embedding context is challenging. Lastly, highly educated individuals better identify asymmetrical and open targets, as well as shapes embedded in complex contexts. In summary, our study clarifies the role of shape properties in disembedding performance and highlights sex differences not been reported so far.